Effect of Extraction Method and Solvent Type on Total Phenolics Content, Total Flavonoid and Antioxidant Activity of Pegagan Extract (Centella asiatica (Linn.) Urban) - Riza, Ahyar; Syafruddin Ilyas; Endang Sjamsudin; Delyuzar Delyuzar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Centella asiatica (CA) or pegagan or horse foot leaves is one of the traditional plants widely used to treat various diseases. This study aims to evaluated the content of total phenolics and total flavonoids, as well as the antioxidant activity of Centella asiatica extracts from different methods and solvents. Methods: The sample was divided into three groups, (70% ethanol maceration, methanol maceration and water infundation). Total phenolic compounds in the extract were determined by the Follin-Ciocalteu method, total flavonoid content was determined by the aluminum chloride colorimetric assay method, and antioxidant activity was assessed by the immersion DPPH free radicals method. Determination data of IC50 was assessed by regression test and differences between the three extract groups were tested by ANOVA or Kruskal Wallis test. Results: The highest total phenolics and total flavonoid were obtained in Centella asiatica extract with water solvent, 251.88 ± 0.96 mg/g GAE and 7.26 ± 0.03 mg/g QE, followed by 70% ethanol and methanol. In addition, the best antioxidant activity was also shown in the extract with water, namely 24.09 ± 0.01. The difference test results between all groups showed significant results (p<0.05) in all parameters. Conclusion: The best content of total phenolic, total flavonoid, and antioxidant activity was obtained by infundation with water solvent. In the maceration method, the best content of the three parameters measured was obtained in the group with ethanol solvent.